2012
DOI: 10.1088/1748-9326/7/3/034031
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal forecasts of northern hemisphere winter 2009/10

Abstract: Northern hemisphere winter 2009/10 was exceptional for atmospheric circulation: the North Atlantic Oscillation (NAO) index was the lowest on record for over a century. This contributed to cold conditions over large areas of Eurasia and North America. Here we use two versions of the Met Office GloSea4 seasonal forecast system to investigate the predictability of this exceptional winter. The first is the then operational version of GloSea4, which uses a low top model and successfully predicted a negative NAO in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 36 publications
6
80
0
Order By: Relevance
“…These cold conditions over North America and Europe coincided with one of the most extreme negative phases of the North Atlantic Oscillation (NAO) in the observational record (e.g. Fereday et al 2012). The North Atlantic jet stream also had an extremely pronounced southward displacement through most of the DecemberFebruary period (Santos et al 2013).…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…These cold conditions over North America and Europe coincided with one of the most extreme negative phases of the North Atlantic Oscillation (NAO) in the observational record (e.g. Fereday et al 2012). The North Atlantic jet stream also had an extremely pronounced southward displacement through most of the DecemberFebruary period (Santos et al 2013).…”
Section: Introductionmentioning
confidence: 74%
“…On the one hand, the winter-mean 500 hPa NAO pattern was better reproduced when the stratosphere was nudged as in Ouzeau et al (2011) using the MeteoFrance Arpege model. Also, the high-top model in Fereday et al (2012) which better resolves the stratosphere and better predicts stratospheric sudden warmings showed improved NAO forecasts. On the other hand, Jung et al (2011) found that nudging the ECMWF forecast model in the stratosphere did not improve NAO forecasts.…”
Section: Role Of the Stratosphere In The Snow/nao Couplingmentioning
confidence: 98%
See 1 more Smart Citation
“…Several mechanisms have been proposed for the anomalously low winter temperatures. These include the teleconnection pattern of the Northern Hemisphere and El Niño-Southern Oscillation (ENSO) and anomalous Eurasian snow cover (Cohen et al 2010), anomalous Arctic sea ice extent (Strey et al 2010), and sudden stratospheric warmings (Fereday et al 2012). The North Atlantic experienced anomalous SSTs during these two winters (Taws et al 2011) and these are known to influence atmospheric circulation over northern Europe (Cassou et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Among all, heat waves are predicted to become more frequent, intense and longer lasting (Karl and Trenberth, 2003;Meehl and Tebaldi, 2004), especially in certain areas like central-western Europe, where the length of summer heat waves has doubled and the frequency of hot days has almost tripled in recent decades (Della Marta et al, 2007). Regarding cold waves, instead, a recent paper foresaw an increased likelihood of cold in the European region (Fereday et al, 2012).…”
Section: Introductionmentioning
confidence: 99%